Study on injection and production of oil and water wells in steam flooding test field of thin oil reservoir. Issue 1 (March 2021) - Yu, Haiwei
Abstract: On the basis of dynamic changes of steam injection wells and extraction wells, the influencing factors of steam injection oil production in transition zone are analyzed and summarized. According to the dynamic relationship of oil-water wells, the feasibility of steam flooding in this zone is analyzed. According to the field conditions, the reasonable well spacing and injection parameters are optimized to provide reliable field data for the application of steam flooding in this zone.